2016
DOI: 10.1039/c6ra08813a
|View full text |Cite
|
Sign up to set email alerts
|

Superior electrocatalytic activity of ultrathin PtPdBi nanowires towards ethanol electrooxidation

Abstract: Bimetallic catalysts, PtBi, PtPd and PdBi have been explored and may be promising candidates for nextgeneration anodic catalysts of direct alcohol fuel cells due to their enhanced catalytic activity and longterm durability. However, ternary PtPdBi alloy catalysts are rarely reported because of the synthetic difficulty in manipulating three metallic precursors. Here, ternary metallic Pt x Pd 93Àx Bi 7 alloy nanowires were prepared for systematically investigating their electrocatalytic activity towards ethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
1
0
1
Order By: Relevance
“…In addition to the ultrathin nanostructure, theoretical calculations and recent research results have also demonstrated that the overall performance of nanowires could be further improved through the modulation of their chemical composition, which has triggered a great effort in the synthesis of bimetal/multimetal nanowires . Heterojunction structures that consist of two or more chemically distinct phases have initiated new investigations with a number of notable advancements.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the ultrathin nanostructure, theoretical calculations and recent research results have also demonstrated that the overall performance of nanowires could be further improved through the modulation of their chemical composition, which has triggered a great effort in the synthesis of bimetal/multimetal nanowires . Heterojunction structures that consist of two or more chemically distinct phases have initiated new investigations with a number of notable advancements.…”
Section: Introductionmentioning
confidence: 99%
“…A quantidade de metais foi calculada pelo produto entre a massa do eletrocatalisador utilizada no eletrodo de trabalho e as porcentagens dos metais. Entretanto, na literatura, além da normalização pela quantidade de metais (ZHANG et al, 2016;CARVALHO et al, 2018), é comum encontrar a normalização pelo teor de platina (BRANDALISE, 2010), paládio (ZHANG et al, 2015) ou platina + paládio (ZHANG et al, 2012), assim a comparação direta entre diferentes trabalhos pode levar o leitor a uma interpretação errônea de resultados.…”
Section: Preparação Dos Conjuntos Eletrodo-membrana-eletrodo (Meas)unclassified